Neuroendocrine neoplasms as a lynch syndrome manifestation: a case report and comprehensive literature review - Bernal Zárate, Maria Paula; Mendivelso-Gonzalez, Daniel Felipe; Torres, William Camilo; González Clavijo, Angelica Maria; Ballen, Diego Felipe; Parra Medina, Rafael; Riaño-Moreno, Julián C. (Frontiers in Endocrinology, 2025)
Lynch syndrome (LS) is an autosomal dominant inherited disorder caused by pathogenic variants in DNA mismatch repair (MMR) genes, most commonly MLH1 and MSH2. LS significantly increases the risk of various cancers, including colorectal, endometrial, gastric, and ovarian malignancies. Neuroendocrine neoplasms (NENs) are rare tumors that arise from neuroendocrine cells, predominantly in the gastrointestinal tract, and are frequently associated with hereditary cancer syndromes such as multiple endocrine neoplasia types 1 and 2. While a definitive association between LS and NENs has not been established, isolated cases have been reported. We present the case of a 63-year-old woman with a history of colorectal cancer and a confirmed LS diagnosis, identified through genetic testing that revealed a pathogenic MLH1 variant. Years later, she developed a grade 2 non-functional neuroendocrine tumor (NET), likely of gastrointestinal origin. The patient underwent surgical resection, followed by treatment with somatostatin analogs. Due to this uncommon presentation, we conducted a literature review to explore the potential relationship between LS and NENs. Our analysis identified 13 additional cases of NENs in LS patients, encompassing NETs, neuroendocrine carcinomas (NECs), and mixed neuroendocrine non-neuroendocrine neoplasms (MiNENs). This growing body of evidence suggests that NENs may be part of the LS tumor spectrum. Further research is needed to elucidate the underlying mechanisms and determine whether LS predisposes individuals to NENs. Enhanced surveillance in LS patients could improve early detection of rare malignancies such as NENs, ultimately expanding our understanding of LS-associated cancer risks and guiding more effective clinical management.